(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
In this study, we developed an inventory model for Indian perishable products by the incorporation of time-dependent holding costs into the model. Demand is influenced by pricing and advertising decisions for Indian perishable products. We take a linear time-dependent holding cost, which shows the insurance and storage cost of perishable products increases over time. Many traditional studies take holding cost as a constant, which cannot match the real scenario. The optimal replenishment cycle is obtained in this inventory model. Numerical and sensitive analysis is done to validate the inventory model for Indian perishable products.